Red phosphorescent trilayer organic light-emitting field-effect transistors with a wide recombination zone. (20th January 2016) - Chang, Jui-Fen; Chen, Wei-Ren; Lai, Yi-Chien; Chien, Fan-Ching
Abstract: We report on red phosphorescent trilayer organic light-emitting field-effect transistors (LEFETs), which exhibit ambipolar transport characteristics but strong emission in the unipolar hole regime, with an exceptionally wide recombination zone of 60–70 µm and a maximum external quantum efficiency of 0.21%. From the results of detailed electroluminescence characterization, we clarify how the energy-level matching condition and transport geometry of the heterostructure govern the charge distribution and recombination, and affect the overall device performance.